Corporate governance antecedents to shareholder activism: A zero‐inflated process. (9th February 2016) - Goranova, Maria; Abouk, Rahi; Nystrom, Paul C.; Soofi, Ehsan S.
Abstract : Research summary: Shareholder activism has become more widespread, yet the role of corporate governance as antecedent to shareholder activism remains equivocal. We propose a new conceptual model that characterizes the stochastic of observable shareholder activism as a compound product of two latent components representing (1) shareholder activists' propensity to target a company and (2) executives' propensity to settle activists' demands privately. Our model explicitly decouples corporate governance expectations for the two latent components embedded in activism process, and thus allows us to relax assumptions of homogenous shareholder interests and constrained managerial discretion where corporate managers are expected to negotiate privately and settle only value‐creating activist demands. Bayesian analysis of zero‐inflated Poisson regression reveals that corporate governance relationships with activism vary across shareholder demands and private settlements. Managerial summary: Increasing shareholder activism has generated debates as to whether activism promotes managerial accountability and responsibility or instead encourages managerial short‐termism. Our research model allows for heterogeneous interests among a company's shareholders. We theorize and empirically investigate a broader role of corporate governance: governance mechanisms need to ensure that executives are not (1) ignoring activists' value‐increasing demands or (2) accommodating activists' value‐decreasing demands in a private, opaque manner that disenfranchises other shareholders. Our results indicate that corporate governance implications differ for visible shareholder demands in contrast with private activism. A plausible application of our model is that it provides estimates of the probability of the numbers of shareholder demands to be received by a firm and the probability of privately settling a demand. Copyright © 2015 John Wiley & Sons, Ltd.